1917 Mont. Laws 179-80 - (:unkn) unknown (My University, 1917)
Ch. 109, § 2: It shall be unlawful for any person at any time to hunt, trap, kill, capture, chase or molest any game animals or game birds whatever within the limits of said game preserve, or to discharge any firearms or to create any unusual disturbance tending to frighten or drive away any game animals or any game birds within said preserve;
Keywords: HUNTING REGULATION